2022
DOI: 10.3390/su14158978
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and Habitat Characteristics Associated with the Occurrence of Peste des Petits Ruminants in Africa

Abstract: As a highly contagious viral disease, peste des petits ruminants (PPR) can cause severe socio-economic impacts in developing countries due to its threat to sheep and goat production. Previous studies have identified several risk factors for PPR at the individual or herd level. However, only a few studies explored the impacts of landscape factors on PPR risk, particularly at a regional scale. Moreover, risk factor analyses in Africa usually focused on sub-Saharan Africa while neglecting northern Africa. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Most studies (71.2%, n = 30) described the temporal trends of PPR epidemics aggregated per day, week, month or year depending on the temporal aggregation of the original data. Generalized Linear Negative Binomial Regression Model (GLNBRM), (11), Generalized Linear Mixed Models (GLMMs) (47), Negative Binomial (45), linear (15,37,48,49) or logistic regression (50,51) models were used to explore or test hypothesis related to temporal trends. Other studies resorted to Bayesian approaches (3,52,53).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies (71.2%, n = 30) described the temporal trends of PPR epidemics aggregated per day, week, month or year depending on the temporal aggregation of the original data. Generalized Linear Negative Binomial Regression Model (GLNBRM), (11), Generalized Linear Mixed Models (GLMMs) (47), Negative Binomial (45), linear (15,37,48,49) or logistic regression (50,51) models were used to explore or test hypothesis related to temporal trends. Other studies resorted to Bayesian approaches (3,52,53).…”
Section: Resultsmentioning
confidence: 99%
“…By including covariates that reflect the circulation of PPRV in wildlife reservoirs like saiga goats, an epidemiological connection between PPRV in wildlife and disease outbreaks in livestock was investigated. For example, closeness to protected, national parks or forest coverage were included in seven analyses (four in Africa and three in Asia) as a representation of a potential livestock–wildlife interaction; among these studies, four reported a positive association between presence or closeness to a protected area and PPR outbreak occurrence; however, this relationship varied across study periods, and locations (11,43,47,57,62,63,69). In general, 47.4% (7/19) of research done in Asia and Africa linked this category of wildlife-livestock interaction to PPR risk.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations